Scope of taxation as a tool of the Environmental Policy of the European Union: Environmental taxes and their effectiveness as an instrumental protection - Montoro López, Ana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The protection and conservation of the environment is shown as one of the greatest concerns of global politics today. Human activities that are negatively influencing the environment have meant for the global community and specifically for the European Union the need to set up a common policy with the aim of curbing environmental deterioration. This paper aims to show how European policy has influenced the configuration and development of environmental taxation as a tool for protecting the environment.